2017
DOI: 10.1002/cbic.201700052
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Computational Investigations of Ligand Binding to IspH: Discovery of Non‐diphosphate Inhibitors

Abstract: Isoprenoid biosynthesis is an important area for anti-infective drug development and one target is IspH, (E)-1-hydroxy-2-methyl-but-2-enyl 4-diphosphate (HMBPP) reductase, which forms isopentenyl diphosphate and dimethylallyl diphosphate from HMBPP in a 2H+/2e− reduction. IspH contains a 4Fe-4S cluster and here, we first investigated how small molecules can bind to the cluster using HYSCORE and NRVS spectroscopies. The results of these as well as other structural and spectroscopic investigations led to the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Co-crystallographic structures of 48 with oxidized IspH were in accordance with the unexpected Mössbauer spectroscopy results and demonstrated that the binding between the alkyne residue and the fourth iron is not direct, indeed a water molecule is in between [ 46 ]. This result was further validated using NRVS measurements of the IspH- 48 complex [ 84 ]. NRVS studies of the free-substrate IspH had previously shown that the apical iron was bound to three sulfide ions of the cluster and to three molecules of water [ 38 ].…”
Section: Isph Inhibitorsmentioning
confidence: 73%
See 4 more Smart Citations
“…Co-crystallographic structures of 48 with oxidized IspH were in accordance with the unexpected Mössbauer spectroscopy results and demonstrated that the binding between the alkyne residue and the fourth iron is not direct, indeed a water molecule is in between [ 46 ]. This result was further validated using NRVS measurements of the IspH- 48 complex [ 84 ]. NRVS studies of the free-substrate IspH had previously shown that the apical iron was bound to three sulfide ions of the cluster and to three molecules of water [ 38 ].…”
Section: Isph Inhibitorsmentioning
confidence: 73%
“…On the other hand, due to the impossibility of studying the oxidized IspH by EPR, the inhibitor 48 was examined by EPR in complex with the reduced IspH. The results obtained by O’Dowd et al [ 84 ] revealed plausible π-interactions between the inhibitor 48 and the reduced [4Fe-4S] cluster.…”
Section: Isph Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations